PELAKSANAAN KEWENANGAN PEMERINTAHAN DESA DALAM PEMENUHAN HAK WARGA KORBAN BENCANA PADA TINGKAT DESA - Achmad Robi Afrilihadi; Mohammad Maiwan; Sanusi (Journal of Civics and Moral Studies, 2025)
This study aims to analyze the implementation of the authority of the village government in fulfilling the rights of disaster victims at the village level. The research problem focuses on how this authority is exercised in practice, how citizens' rights are fulfilled, and the obstacles faced by village governments in disaster situations. The research uses a descriptive method with a qualitative approach. Data collection was carried out through in-depth interviews, field observations, and documentation using triangulation techniques. The subjects of the study include village government officials and residents affected by the disaster. The results of the study show that the authority of the village government in handling disasters is still dominated by emergency response and the implementation of administrative tasks. The village government plays an important role as the closest actor to the residents, but the authority exercised is limited and highly dependent on coordination with the local government. The fulfillment of the rights of disaster victims is more realized in the form of short-term material assistance, while the fulfillment of rights in the dimension of sustainable social protection has not been optimal. The main obstacles faced by village governments include limited institutional capacity, resources, inter-agency coordination, and a top-down policy approach. These findings confirm that disaster management at the village level is an important space for the practice of regional autonomy and citizenship.